Hot chocolate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Cocoa prices increased sharply to a 17-year record of more than 2,000/t in October 2002. Rotting harvests due to too much rainfall in Ghana and the outburst of civil unrest following the September coup attempt in Côte d Ivoire, where 40% of the...